2020
DOI: 10.1101/2020.12.16.423154
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A native chemical chaperone in the human eye lens

Abstract: Cataract is one of the most prevalent protein aggregation disorders and still the most common cause of vision loss worldwide. The metabolically quiescent core region of the human lens lacks cellular or protein turnover; it has therefore evolved remarkable mechanisms to resist light-scattering protein aggregation for a lifetime. We now report that one such mechanism involves an unusually abundant lens metabolite, myo-inositol, suppressing aggregation of lens crystallins. We quantified aggregation suppression us… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
(201 reference statements)
0
2
0
Order By: Relevance
“…In mature lens fiber cells, ATP, GSH, myo-inositol, NADPH, and polyols are needed to preserve protein solubility and SRO and to protect against light scattering and opacity. Several publications summarize the importance of lens metabolism to the maintenance of protein solubility, stability, structure, symmetric microcirculation, and resist oxidative and osmotic stress (87,93,(249)(250)(251)(252)(253)(254)(255)(256)(257).…”
Section: Metabolic Adaption and Lens Transparencymentioning
confidence: 99%
“…In mature lens fiber cells, ATP, GSH, myo-inositol, NADPH, and polyols are needed to preserve protein solubility and SRO and to protect against light scattering and opacity. Several publications summarize the importance of lens metabolism to the maintenance of protein solubility, stability, structure, symmetric microcirculation, and resist oxidative and osmotic stress (87,93,(249)(250)(251)(252)(253)(254)(255)(256)(257).…”
Section: Metabolic Adaption and Lens Transparencymentioning
confidence: 99%
“…Several studies by others have reported the existence of small molecules that bind to γ-crystallins, including lanosterol ( 59 ), cochineal carmine ( 60 ), ortho-Vanilin ( 61 ), quercetin ( 62 ), hesperetin ( 63 ), and sodium citrate ( 64 ). Moreover, small molecules with either demonstrated potential anticataract properties involving antiaggregation activity against crystallins include rosemarinic acid ( 65 ), morin ( 66 , 67 ), 25-hydrocholesterol ( 68 ), epigallocatechin gallate ( 69 ), and myoinositol ( 70 ). Among these compounds, those that were included in the screen included epigallocatechin gallate, which improved aggregation, whereas morin, lanosterol, hesperetin, and carmine had no impact.…”
Section: Discussionmentioning
confidence: 99%